Deception of public opinion in international politics... creating the enemy in American politics as an example - Dawara, Doctor teacher Raji Naseer (The college of law and political science journal, 2023)
The "enemy innovation " is one of the strategies known since ancient times, and is still being followed, in making the internal and external policy of states and political systems. Making the enemy in domestic politics, especially in totalitarian and dictatorial regimes, is used to escape from internal problems, get rid of political opponents, and strike opposition to the ruling authority. As for the level of international relations, the enemy is used by the major and colonial powers, led by the United States, which desires to impose its hegemony over other countries and peoples according to the logic of unipolarity, to justify wars and the occupation of states, under the pretext of threatening the country or the American or global national security as it is sometimes called, for the purposes of camouflage, and in both cases, the goal of making the enemy is to overturn the facts and falsify In reality, in order to deceive public opinion and entice it to pass policies, the media, both traditional and new, play a major role in persuading and coaxing public opinion and deceiving it, and thus in passing the policies set by decision-makers and owners of international projects.